Down to the wire - Sargeant, Patricia (Harlequin romantic suspense, 2023)
"On the trail of a hacker, IT security expert Malachi Touré finds...a woman from his past he's never gotten over. Dr. Grace Blackwell is no hacker. She's a medical researcher, and someone has stolen a potentially deadly formula from her computer. Despite the still-simmering attraction between them, Mal is wary of trusting her again. Then everything changes when a killer has Grace in their sights..." -- Page [4] cover.